2013
DOI: 10.5137/1019-5149.jtn.8707-13.2
|View full text |Cite
|
Sign up to set email alerts
|

Surgical resection of a complex multiple scalp avf without preoperative embolization: a case report

Abstract: Complex multiple arteriovenous fistula (AVF) of the scalp is an extremely rare disease and the traditional treatment is either endovascular embolization or surgical resection with preoperative endovascular embolization. Here, a 34-year-old male with pulsating mass and multiple tortuous vessels in front of the left tragus and scalp who was diagnosed as complex multiple arteriovenous fistula of the scalp is presented. Nearly total surgical resection of the lesion without preoperative intervention was performed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 11 publications
(15 reference statements)
0
12
0
Order By: Relevance
“…Scalp arteriovenous fistula (sAVF) is a rare vascular disease and previously named also as cirsoid aneurysms; therefore, only small case series have been reported by literature [1][2][3][4][5][6]10]. It is widely believed that sAVF may be of either congenital or posteriori reason, and the latter one is the most common cause of lesion, which mainly results from head trauma or iatrogenic injury such as head surgery, hair transplantation, and scalp vein infusion [1][2][3][4][7][8][9][10]. In most of the patients, superficial temporal artery (STA) was involved.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Scalp arteriovenous fistula (sAVF) is a rare vascular disease and previously named also as cirsoid aneurysms; therefore, only small case series have been reported by literature [1][2][3][4][5][6]10]. It is widely believed that sAVF may be of either congenital or posteriori reason, and the latter one is the most common cause of lesion, which mainly results from head trauma or iatrogenic injury such as head surgery, hair transplantation, and scalp vein infusion [1][2][3][4][7][8][9][10]. In most of the patients, superficial temporal artery (STA) was involved.…”
Section: Discussionmentioning
confidence: 99%
“…In most of the patients, superficial temporal artery (STA) was involved. After injury of the STA, hemodynamic begins to change and is characterized by high flow from the abundant feeding artery leading to a progressive venous dilation in the scalp [ 2 , 3 , 5 , 8 , 9 ]. The sAVF generally present with small subcutaneous swelling in the beginning, which can enlarge to become a pulsatile scalp mass over time and cause severe cosmetic deformity [ 2 , 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They also reported that the five patients treated by a combination of endovascular treatment + surgical treatment were free of recurrence or complications. 11) Various endovascular procedures have been reported, embolic agents such as Onyx, NBCA, coils, polyvinyl acetate, and ethanol have been used, and techniques including direct puncture using a circular compression device (CCD) 12) and transvenous embolization by Onyx injection using a balloon 13) have been reported.…”
Section: Discussionmentioning
confidence: 99%